ENHANCED USER EXPERIENCE IN DATA MONITORING VIA MICROSOFT SHAREPOINT AND POWER BI - Rashidi, Muhammad Norashid Hakimmi Bin; Salleh, Alia Binti Abdullah; Mokhtar, Seri Bunian Binti; Awang, Mariah Binti; Sari, Kamarul Aini Binti (Lembaga Penelitian dan Pengabdian Masyarakat, Institut Teknologi Nasional (ITN) Malang, 2023)
The study that was carried out aimed to examine the important and suitable data parameters with workers in facility management fields and to propose a new technique integrating digitalized data for a few facility management companies in Malaysia. The new parameter that was proposed was to use Microsoft SharePoint and Power BI. Microsoft SharePoint offered the ability to track both major and minor document version changes. To enforce versioning and handle changes cleanly, libraries could be set to require users to check documents in and out when making changes to content. Some parameters for Microsoft SharePoint included its ability to run in the cloud with Microsoft Office 365, allowing for easy sharing of content and information across multiple places and devices. On the other hand, Microsoft Power BI simply and effectively designed and showed data analysis and presentations. In addition, it enabled the creation of reports at a fraction of the cost of more conventional systems and with far less rigidity and overhead. Parameters for Microsoft Power BI included choosing the right visualization type, customizing visualization properties, considering custom visualizations, and removing unnecessary elements in high-density reports. The study was conducted using two methods, namely quantitative and qualitative. For the quantitative method, a questionnaire approach was used, with the questionnaire distributed to several employees in the field of facility management in Malaysia. The qualitative method used an interview approach with several employees in the facility management field who were selected based on the questions. After the distribution of questionnaires, it was found that some companies or facility management work fields still used manual methods in recording their data. Some respondents had also used CMMS or advanced software but agreed with the method that had been suggested to them. The result of the first objective was the ability to understand that there were many parameters that were important for data documentation in the FM sector. Regarding the second objective result, it was observed that the majority of respondents who had completed the questionnaire agreed with the idea of proposing a new parameter to integrate digitalized data for a few facility management companies in Malaysia.